PECULIARITIES OF CONTAMINATION OF THE BLACK SEA - Biliavskiy, George O.; Golod, Armine V. (Proceedings of National Aviation University (archive), 2009)
Article is devoted to meaningfulness estimation of some factors in forming ecological conditions in regions of the Black Sea. Comparative estimation of anthropogenic contamination degree of sea regions environment considered. The regions the most unhappy in ecological attitude are defined, that allows to mark first and foremost arrangements on improvement of ecological situation of the Black Sea.